Visual field examination method using virtual reality glasses compared with the Humphrey perimeter - Tsapakis S (Dove Medical Press, 2017)
Stylianos Tsapakis, Dimitrios Papaconstantinou, Andreas Diagourtas, Konstantinos Droutsas, Konstantinos Andreanos, Marilita M Moschos, Dimitrios Brouzas 1st Department of Ophthalmology, National and Kapodistrian University of Athens, Athens, Greece Purpose: To present a visual field examination method using virtual reality glasses and evaluate the reliability of the method by comparing the results with those of the Humphrey perimeter.Materials and methods: Virtual reality glasses, a smartphone with a 6 inch display, and software that implements a fast-threshold 3 dB step staircase algorithm for the central 24° of visual field (52 points) were used to test 20 eyes of 10 patients, who were tested in a random and consecutive order as they appeared in our glaucoma department. The results were compared with those obtained from the same patients using the Humphrey perimeter.Results: High correlation coefficient (r=0.808, P<0.0001) was found between the virtual reality visual field test and the Humphrey perimeter visual field.Conclusion: Visual field examination results using virtual reality glasses have a high correlation with the Humphrey perimeter allowing the method to be suitable for probable clinical use. Keywords: visual fields, virtual reality glasses, perimetry, visual fields software, smartphone